Anemia and Micronutrient Deficiencies in the First Trimester of Pregnancy Among Women in Eastern Maharashtra, India. (14th June 2022) - Gugel, Abigail; Bhaise, Shilpa; Lauer, Jaqueline; Patel, Archana; Hibberd, Pat; Locks, Lindsey
Abstract: Objectives: Maternal anemia during pregnancy increases the risk of a myriad of negative birth outcomes, including maternal mortality, neonatal mortality, and low birth weight. In Eastern Maharashtra, India, the prevalence of anemia among pregnant women has been reported to be > 80%. While the most common cause of anemia is iron deficiency, its relative contribution is often unknown, as are rates of other key micronutrient deficiencies including B12 and folic acid. The primary objectives of this study are 1) to determine the prevalence of micronutrient deficiencies (iron, folic acid, and B12) and 2) to quantify the contribution of these micronutrient deficiencies to anemia among pregnant women in Nagpur (Eastern Maharashtra, India). Methods: We conducted a cross-sectional study of 200 women from four clusters in Nagpur. In the first trimester of pregnancy, trained nurses collected venous blood samples and we used Hemocue on blood samples collected with a finger prick. Anemia was defined as hemoglobin < 110 g/L, iron deficiency as serum ferritin < 15 µg/mL (adjusted for inflammation), folic acid deficiency as serum folic acid < 3 ng/mL, and B12 deficiency as < 203 pg/mL. Results: Among women in our sample, 37.5% were anemic, 40.0% were iron deficient, 30.0% were vitamin B12 deficient, and none were folic acid deficient. Hemocue assessment of capillary blood yielded a prevalence of anemia of 50.0%. Approximately half (53.0%) of women diagnosed with anemia via Hemocue were iron deficient and 31.0% were vitamin B12 deficient. We did not find any folate deficiency in this population. Conclusions: We found the prevalence of anemia in Eastern Maharashtra to be lower compared to previous studies collecting capillary blood, though still unacceptably high. Furthermore, as only half of anemia cases were associated with iron deficiency, iron and folic acid (IFA) supplementation programs may only partially ameliorate the high prevalence of anemia. Funding Sources: This study was funded by the Thrasher Research Fund grant.